District heating and electricity production based on biogas produced from municipal WWTPs in Turkey: A comprehensive case study. (15th May 2021) - Abusoglu, Aysegul; Tozlu, Alperen; Anvari-Moghaddam, Amjad
Abstract: In this paper, district heating (DH) potentials of the wastewater treatment plants (WWTPs) based on their biogas, electricity, and heat productions are considered. Two district heating scenarios are developed: (i) DH Scenario I which is based on both excess biogas storage of the WWTP and exhaust gas of the cogeneration with the actual power output, (ii) DH Scenario II which is based on the exhaust gas of the cogeneration with the increased power output using all the biogas produced. In DH Scenario I, it is found that 458 dwellings can be heated via the DH system proposed considering only the waste heat of the cogeneration. In addition, the natural gas consumption of 1112 dwellings with the same annual heating load can also be met using the purified biogas. In DH Scenario II, the electricity production could be increased to 1643 kWh by burning all the biogas produced in the cogeneration plant. In this scenario, the annual heating load of 755 dwellings in Gaziantep province can be covered using the waste heat in the DH system. The payback period for the DH Scenario I is calculated as 2.5 years, while for the DH Scenario II, it is obtained as 2 years. Highlights: DH and electricity production potentials of the WWTPs are considered. Two DH and electricity production scenarios are developed. Heat demand of 458 dwellings can be met with DH system developed in Scenario I. Heat demand of 755 dwellings can be met with DH system developed in Scenario II. Electricity production can be increased to 1643 kW with Scenario II.